2019
DOI: 10.1007/s00603-019-01941-2
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Experiments on Bowland and Posidonia Shale—Part II: Creep Behavior at In Situ pc–T Conditions

Abstract: To unravel their long-term creep properties at simulated reservoir conditions, we conducted constant stress deformation experiments at elevated confining pressures, p c = 50-115 MPa, and temperatures, T = 75-150 °C, on Posidonia (GER) and Bowland (UK) shale, which exhibit varying petrophysical and mechanical properties. Depending on applied p c-T conditions and sample composition, recorded creep curves exhibit either only a primary (decelerating) or additionally a secondary (quasi-steady state) and a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 70 publications
1
31
1
Order By: Relevance
“…All rights reserved. shown that (primary) creep is mainly accommodated by pore volume compaction and bending of clay minerals (Herrmann et al, 2020). Sone and Zoback (2013b) note that the correlation is generally evident in samples from a single shale unit but cannot be extrapolated to all shales, as other factors also influence the propensity for a shale to creep.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…All rights reserved. shown that (primary) creep is mainly accommodated by pore volume compaction and bending of clay minerals (Herrmann et al, 2020). Sone and Zoback (2013b) note that the correlation is generally evident in samples from a single shale unit but cannot be extrapolated to all shales, as other factors also influence the propensity for a shale to creep.…”
Section: Accepted Articlementioning
confidence: 99%
“…Q. Zhang et al (2014) state that in ideal linear viscoelastic materials that creep deviatorically with no volume change, the relationship between the triaxial and indentation creep modulus (Mighani et al, 2019) and triaxial testing (Herrmann et al, 2020).…”
Section: Comparison With Triaxial Creepmentioning
confidence: 99%
“…This importance has motivated a number of experimental investigations into creep of shale at multiple scales (eg, Refs. 9–20).…”
Section: Introductionmentioning
confidence: 99%
“…This bilayer representation is a simple but promising approach. It is well justified by the fact that shale creep is mainly attributed to the clay and organic constituents rather than the hard minerals, 9,11,13,16,17,19 and it naturally captures the transverse isotropy resulting from the depositional process.…”
Section: Introductionmentioning
confidence: 99%
“…e FEM can also provide useful guidance for the design and construction of new high CFRDs by optimizing dam body structures, construction procedures, and dam construction materials [8]. In order to obtain the creep model of rockfill for FEM simulations, researchers have conducted large-scale triaxial tests for investigating the time-dependent behavior of coarse granular materials under different stress paths, confining pressures, and moisture contents [28][29][30][31][32][33][34][35][36][37]. e analyses reveal that creep deformation of the rockfill is caused by stress redistribution in the dam body associated with a process of abrasion of sharp corners of stones, particle shape, and particle breakage [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%